ANALISIS PENGGUNAAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN CANVA DALAM KEAKTIFAN BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA SEKOLAH DASAR - Elvi Fitri, Alia; Agustin, Viora; Adrias; Azmi Alwi, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low level of students’ learning activeness in Pancasila Education at the elementary school level, which is still dominated by conventional teaching methods. This condition causes students to be less actively involved in the learning process. This study aims to analyze the use of the Problem Based Learning (PBL) model assisted by Canva in improving students’ learning activeness in Pancasila Education for elementary school. The research method used is a qualitative approach with a descriptive type of study. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results of the study indicate that the use of the Problem Based Learning (PBL) model assisted by Canva is able to improve students’ learning activeness, as seen from increased student participation in discussions, greater confidence in asking and answering questions, and involvement in group activities. In addition, the use of Canva helps attract students’ attention and facilitates understanding of the material. Thus, the implementation of the Problem Based Learning (PBL) model assisted by Canva can be an effective alternative in improving students’ learning activeness in Pancasila Education at the elementary school level.